2016
DOI: 10.1051/kmae/2016031
|View full text |Cite
|
Sign up to set email alerts
|

First report of the intracellular fish parasite Sphaerothecum destruens associated with the invasive topmouth gudgeon (Pseudorasbora parva) in France

Abstract: -Sphaerothecum destruens has emerged as a serious parasite of fish. Its life cycle, as well as its association with Asian cyprinids, allows it to infect a wide range of hosts. The topmouth gudgeon (Pseudorasbora parva), an invasive species that has rapidly colonized Europe, has been shown to be a healthy carrier of the parasite. However, in France, the presence of S. destruens and its possible association with P. parva have not yet been demonstrated. Here, we screened topmouth gudgeon DNA for S. destruens usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…What remains an enigma, however, is the discrepancy between the magnitude of observed and predicted mortalities following S. destruens ’ emergence and the low level, virtually absent monitoring and reporting of S. destruens presence across Europe. Only four countries have tested for the presence of S. destruens and all have found the disease present in native and P. parva populations (Andreou et al., ; Spikmans et al., ; Ercan et al., ; Charrier, Peudpiece, Lesne, & Daniel, ; Boitard, Charrier, Labrut, & Jamin, ). Based on the recent work by Hardouin et al.…”
Section: Disease Risk and Early Warning Response: A Controversymentioning
confidence: 99%
“…What remains an enigma, however, is the discrepancy between the magnitude of observed and predicted mortalities following S. destruens ’ emergence and the low level, virtually absent monitoring and reporting of S. destruens presence across Europe. Only four countries have tested for the presence of S. destruens and all have found the disease present in native and P. parva populations (Andreou et al., ; Spikmans et al., ; Ercan et al., ; Charrier, Peudpiece, Lesne, & Daniel, ; Boitard, Charrier, Labrut, & Jamin, ). Based on the recent work by Hardouin et al.…”
Section: Disease Risk and Early Warning Response: A Controversymentioning
confidence: 99%
“…In France, invasive populations of P. parva were first reported in 1980 [33] and a survey of fish populations conducted between 1990-2009 showed that this non-native species has spread dramatically [34]. In 2016, Charrier et al [35] showed the presence of S. destruens in 12 individuals of P. parva caught in a small tributary stream of the Adour River, near Dax, France [35]. Just one year later, Boitard et al [36] reported the occurrence of two additional natural infections of salmonids in France.…”
Section: Of 33mentioning
confidence: 99%
“…In France, invasive populations of P. parva were first reported in 1980 [33] and a survey of fish populations conducted between 1990-2009 showed that this non-native species has spread dramatically [34]. In 2016, Charrier et al [35] showed the presence of S. destruens in 12 individuals of P. parva caught in a small tributary stream of the Adour River near Dax, France [35]. Just one year later, Boitard et al [36] reported the occurrence of two additional natural infections of salmonids in France.…”
Section: Worldwide Distribution Of Sphaerothecum Destruensmentioning
confidence: 99%